DOI: 10.11606/d.100.2019.tde-05062019-205509
|View full text |Cite
|
Sign up to set email alerts
|

Nível de atividade física em adultos paulistanos: uma análise de tendência

Abstract: Agradeço ao meu orientador Alex Antonio Florindo pela amizade, compreensão e segura orientação ao longo deste processo de formação. Às amigas Ana Paula Barbosa e Michele Santos Cruz pela amizade e pelas horas de conversa e incentivo. Agradeço também a todos os colegas do Grupo de Estudos e Pesquisas Epidemiológicos em Atividade Física e Saúde (GEPAF) pela amizade e incentivo. Pois todas estas pessoas foram importantes na construção deste trabalho. RESUMO DIAS, Tulio Gamio. Nível de atividade física em adultos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(33 reference statements)
0
1
0
3
Order By: Relevance
“…For finally, actions and programs coordinate by City Hall authorities that exploit the built environment creating open streets for people during the weekends, as it is done for Minhocão, are important population-level interventions with the potential to reach a large number of people, contributing to the World Health Organization Global Action Plan for physical activity promotion [39]. These efforts are important to continue with good results in public health like an increase of 7.8% in LTPA populations levels among adults residing in São Paulo between 2006 and 2016 [40]. Such initiatives are especially relevant amid the COVID-19 pandemic, where recent Brazilian epidemiological studies have revealed a decline in LTPA among adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…For finally, actions and programs coordinate by City Hall authorities that exploit the built environment creating open streets for people during the weekends, as it is done for Minhocão, are important population-level interventions with the potential to reach a large number of people, contributing to the World Health Organization Global Action Plan for physical activity promotion [39]. These efforts are important to continue with good results in public health like an increase of 7.8% in LTPA populations levels among adults residing in São Paulo between 2006 and 2016 [40]. Such initiatives are especially relevant amid the COVID-19 pandemic, where recent Brazilian epidemiological studies have revealed a decline in LTPA among adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…Com isso, muitas pessoas procuram pelas atividades de aventura na natureza, pois essas proporcionam mais satisfação e prazer, além de também atingir o objetivo de melhorar a saúde (BERTOLI et al, 2015). Há consenso na literatura científica de que para obter uma melhora na saúde do ponto de vista biológico, temos que praticar algum tipo de atividade física (DIAS et al, 2020). Infelizmente no Brasil contamos um um baixo nível de adeptos, e com isso temos uma grande parte da população sedentária.…”
Section: Atividades De Aventura Na Naturezaunclassified
“…Lazer e Saúde Mental em Tempo de COVID-19 Suzy Kamylla de Oliveira MenezesNas subseções a seguir os estudos foram analisados em duas categorias: Saúde mental e COVID-19 e Lazer e COVID-19.Nesta seção foram analisados doze estudos relacionados à saúde mental e COVID-19 (BEZERRA et al, 2020;ZHANG;MA, 2020;MAIA;DIAS, 2020;BARROS et al, 2020; DUARTE et al, 2020;JOHNSON; SALETTI-CUESTA, TUMAS, 2020;FERREIRA et al 2020; ALKHAMEES et al, 2020;ZHANG et al, 2020;LAN;LONG; HANH, 2020;ZHOU et al, 2020;ELMER;MEPHAM; STADTFELD, 2020).Bezerra et al (2020) realizaram um estudo com o objetivo de caracterizar o perfil da população brasileira em isolamento social e identificar preditores de estresse psicossocial. A pesquisa foi quantitativa, descritiva e analítica, realizada de 10 a 12 de abril de 2020, com dados coletados através de questionário online.…”
unclassified